Children’s Position on a Defective Marriage (Fasid) in Terms Establishment of Inheritance Right as an Effort for Legal Certainty - Ivo Junia Imako Haris (Sociological Jurisprudence Journal, 2024)
Marriage in the legal system in Indonesia is said to be valid if it is carried out according to each religion and belief and must be registered based on the applicable provisions. To avoid the occurrence of a defective marriage (fasid), then when a marriage has been carried out based on religion and belief, then the marriage must be registered. this is to avoid any legal consequences that will arise especially for children born in said marriage to the legal status and position of children born in defective marriages (fasid) as heirs. The purpose of this research is to find out the position of children born from broken marriages in terms of determining inheritance rights. This type of this research is normative, which is legal research conducted through library research. The findings of this study indicate that the legal status of children born from defective marriages (fasid) are children out of wedlock which the legal status is recognized by both parents and are not children born from acts of adultery. Regarding the right to inherit a child out of wedlock from a defective marriage (fasid) which has been proven through a DNA test to have a biological relationship with the father and his father’s family, the father and his father’s family as the heir can provide a testamentary grant through a legal act of a will grant which is proven by a notarial deed as a form of inheritance rights but the share may not exceed 1/3 of the heir’s inheritance.